أثر محددات التحول إلى المعايير الدولية لإعداد التقارير المالية "IFRS" في استيفاء متطلبات التحول إلى المعايير الدولية: دراسة ميدانية في مكاتب المراجعة بولاية الخرطوم - السودان - محمد، فتح الإله محمد أحمد; أبكر، عبدالجلال عثمان إدريس (جامعة العلوم والتكنولوجيا, 2023)
تناولت الدراسة أثر محددات التحول إلى المعايير الدولية لإعداد التقارير المالية (IFRS) في استيفاء متطلبات التحول إلى المعايير الدولية، دراسة ميدانية في مكاتب المراجعة بولاية الخرطوم- السودان، حيث هدفت إلى الوقوف على متطلبات التحول إلى هذه المعايير، ومن ثم التعرف على المحددات التي تحد من عملية التحول لهذه المعايير، وأثرها في استيفاء متطلبات التحول إلى المعايير الدولية من وجهة نظر مراجعي الحسابات وذلك باستخدام المنهج الوصفي التحليلي، وقد جرى تقسيم هذه المحددات إلى محاور تمثلت في مجلس تنظيم مهنة المحاسبة والمراجعة بالسودان، والشركات، وسوق الأرواق المالية، والمؤسسات التعليمية. ولتحقيق أهداف الدراسة جرى إعداد استمارة استبيان وزعت على مجتمع الدراسة المتمثل في مكاتب المراجعة بولاية الخرطوم- السودان حيث بلغت عينة الدراسة (220) مفردة من مراجعي الحسابات بولاية الخرطوم. وتوصلت الدراسة إلى نتائج عديدة، أهمها أن أهم متطلبات استيفاء التحول إلى المعايير الدولية لإعداد التقارير المالية في مكاتب المراجعة بولاية الخرطوم- السودان، هو تعزيز المعرفة المحاسبية بالمعايير الدولية لإعداد التقارير المالية لدى ممارسي مهنة المحاسبة، كما توجد محددات عديدة أدت إلى عدم الاهتمام بتبني المعايير الدولية لإعداد التقارير المالية مكاتب المراجعة بولاية الخرطوم- السودان من أبرزها عدم وجود خطة وطنية واضحة لتبن جزئي لهذه المعايير أو توافقها مع المعايير المحلية، ارتفاع تكاليف التحول إلى تطبيق وتبني المعايير الدولية لإعداد التقارير المالية، بالإضافة إلى التخوف من متطلبات الإفصاح الإضافية لمعايير الدولية لإعداد التقارير المالية. The study examined International Financial Reporting Standards (IFRS), the factors influencing their adoption in the Sudanese business environment, and proposed solutions. The aim was to identify the requirements for adopting these standards in the Sudanese business environment. In addition, to identify the determinants that hinder the transition to these standards from an auditor's perspective by using a descriptive analytical approach. These determinants were divided into categories represented by the Accounting and Auditing Profession Regulatory Council in Sudan, companies, the securities market, and educational institutions. A questionnaire was used to collect study data from the study population which represented in the audit offices in the state of Khartoum – Sudan, and the study sample consisted of (220) participants. The main study findings are: the most important requirement for fulfilling the transition to international standards for the preparation of financial reports in the Sudanese business environment is to enhance the accounting knowledge of international standards for the preparation of financial reports among the practitioners of the accounting profession. There are also several determinants that have led to a lack of interest in adopting international standards for preparing financial reports in the Sudanese business environment, the most prominent of which are the absence of a clear national plan to partially adopt these standards or their compatibility with local standards, the high costs of switching to applying and adopting international financial reporting standards, In addition to apprehension about the additional disclosure requirements of the International Financial Reporting Standards.
Keywords: التقارير المالية -- المعايير الدولية -- مراجعو الحسابات -- الاستثمارات الدولية